2016
DOI: 10.1016/j.jcsr.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic lateral response of FRP-confined circular concrete-filled steel tubular columns

Abstract: Concrete-filled steel tubular (CFT) columns are widely used as columns in many structural systems and a common failure mode of such tubular columns is inelastic outward local buckling near a column end. The use of fibre-reinforced polymer (FRP) jackets/wraps for the suppression of such local buckling has recently been proposed and has been proven to possess excellent potential in both retrofit/strengthening and new construction. This paper presents the results of an experimental study into the behaviour of lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…To improve the durability of the outer steel tube of CFT and STCC elements under aggressive environments, and to avoid or delay the early age local buckling of steel tube of CFT elements, several researchers proposed using FRP wrap to confine CFT (FRP-CFT, Fig. 1d) [20][21][22][23][24][25][26][27][28] or STCC (FRP-STCC, Fig. 1e) [29] elements.…”
Section: Monotonic Axial Compressive Behaviour and Confinementmentioning
confidence: 99%
“…To improve the durability of the outer steel tube of CFT and STCC elements under aggressive environments, and to avoid or delay the early age local buckling of steel tube of CFT elements, several researchers proposed using FRP wrap to confine CFT (FRP-CFT, Fig. 1d) [20][21][22][23][24][25][26][27][28] or STCC (FRP-STCC, Fig. 1e) [29] elements.…”
Section: Monotonic Axial Compressive Behaviour and Confinementmentioning
confidence: 99%
“…In 2005, Xiao et al (2005 performed a study to introduce and experimentally validate FRP-confined CFST columns under axial and seismic loads and confirmed the excellent seismic performance of these columns. Recently, several studies were reported to examine the constitutive behaviour of FRP-confined CFST columns (Xiao et al 2005, Liu and Lu 2010, Park et al 2010, Tao et al 2011, Lin 2012, Teng et al 2013, Park and Choi 2013, Hu and Seracino 2013, Wang et al 2015,Yu et al 2016, but more studies are underway to examine details of the elements.…”
Section: Introductionmentioning
confidence: 99%
“…Many quasi‐static cyclic loading tests have been conducted to investigate the seismic behavior of conventional circular CFST columns, but they concentrated mainly on NS concrete and NS steel . Meanwhile, Elremaily and Azizinamini studied the seismic behavior of six circular CFST columns with a concrete cylinder compressive strength varying from 40 to 104 MPa and NS steel ( f y = 372 MPa) with D / t ratios of 51 and 34.…”
Section: Introductionmentioning
confidence: 99%
“…Their studies revealed that the use of HS steel tubes could provide a larger elastic deformation capacity and a better confining effect than NS steel tubes under small‐ D / t ratios and that HS core concrete could delay local buckling until the occurrence of a large rotation. Nevertheless, for circular HCFTST columns, an uncertainty in the composite action still exists due to out‐of‐code D / t ratios; very few experimental studies within the aforementioned literature considered the seismic behavior of circular HCFTST columns with out‐of‐code D / t ratios.…”
Section: Introductionmentioning
confidence: 99%